RANCANG BANGUN UNIPOLAR PWM UNTUK PENGENDALIAN RANGKAIAN H-BRIDGE MENGGUNAKAN OPERATIONAL AMPLIFIER - Asmar Asmar (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2014)
Unipolar PWM control technique carried out by comparing triangular wave with two control voltages. The resulting pulses are used to control H-Bridge circuit. The technique can be done by using the functions of the operational amplifier. There are three main circuits needed is a triangular wave circuit, voltage control circuit, and a comparator circuit. With proper adjustment between the triangular waves and voltage control, voltage regulation will be obtained smooth.